Analisis Kelengkapan Pengisian Laporan Operasi pada Tindakan Sectio Caesarean di Rumah Sakit Buah Hati Pamulang - Rumondang Christin; Dede Resa Oktaviani; Gama Bagus Kuntoadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The operation report form is a report or record of the surgical procedure on the patient. The operation report form is used to report and record the patient's condition before, during, and after receiving surgery. The type of research used is descriptive with a quantitative approach. Data collection using observation results and check list sheets. The population of this study was 200 operation report forms on sectio caesarea at RSIA Buah Hati Pamulang in March - May 2025. The sample of this study was 133 operation report forms on sectio caesarea with simple random sampling technique. From The results of the study found that the patient identity component was filled in completely, namely 100%, in the important report sub-component almost completely filled in with a percentage of 94% and there was a post-surgical diagnosis sub-component that was only mostly with the lowest percentage of 8%, in the researcher's authentication component there was a sub-component of the surgeon's TTD which was almost completely filled in with a percentage of 99%, and and there was a percentage of almost completely complete, namely 99% assistant anesthesiologist 98%, It is recommended for RSIA Buah Hati Pamulang to immediately use the electronic operation report form in accordance with PMK 24 of 2022 concerning Medical Records governing Electronic Medical Records in health service facilities (fasyankes) in Indonesia.